2019
DOI: 10.1111/padm.12572
|View full text |Cite
|
Sign up to set email alerts
|

Public sector employees in a challenging work environment

Abstract: Public sector employees are expected to perform well in a work environment that is characterized by a variety of challenges. This Symposium aims to shed light on how environmental changes impact the shared identity, attitudes and behaviour of public sector employees; how public sector employees take charge of continuous change and deal with challenges in their work environment;and how organizations can help employees to tackle such workrelated challenges. We identify four specific gaps in literaturesome method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…While several past studies suggested that the activities of automation would replace human labor [5], other studies revealed that the knowledge worker and machine will complement each other [24][25][26]. Very little of the existing literature could highlight how knowledge workers' activities and automation have changed the entire structure of the organization.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…While several past studies suggested that the activities of automation would replace human labor [5], other studies revealed that the knowledge worker and machine will complement each other [24][25][26]. Very little of the existing literature could highlight how knowledge workers' activities and automation have changed the entire structure of the organization.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…This can be interpreted as a worrying trend as research suggests that the increasing workload is unfortunate to organizational performance because it fosters intentions to quit one’s job and it lowers job satisfaction (Gould-Williams et al, 2014). This makes it important for HRM studies to increase our understanding of how public sector employees can be managed in a challenging work environment (Bauwens et al, 2019a; Steen & Schott, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies have reported significant institutional and social factors in terms of productivity, trust in government, improved management practices, and accountability in the public sector [51]. However, performance management is also considered a significant factor, since public sector employees are expected to perform well in a challenging work environment [52]. Finally, the public sector is considered significant in terms of strategic management.…”
Section: Public Sector Downsizingmentioning
confidence: 99%